PENINGKATAN HASIL BELAJAR SISWA DENGAN PENERAPAN MODEL PROBLEM BASED INSTRUCTION PADA MATA PELAJARAN EKONOMI - Sri Abidah Suryaningsih, ; Asti Prasmawawti, (Pendidikan Ekonomi, 2010)
The current study is intended to examine how the students learning results in economics subject matter was after the use of problem based instruction model, and how the teacher managed the class with problem based instruction,  how the students activities in the instructional activities, and how the responded the use of the problem based instruction. The subjects were 32 students of class X-A of SMA Negeri 2 Mejayan in the academic year 2010-2011, while the object was problem based instruction (PBI). The result shows that the students learning results increased after the use of PBI. The activities of students and teacher also got improved in the three cycles. The students showed positive responses towards the use of problem based instruction.